Boronic acid based dynamic click chemistry: recent advances and emergent applications. Issue 5 (17th December 2020) - Chatterjee, Saurav; Anslyn, Eric V.; Bandyopadhyay, Anupam
Abstract : Fundamental progress, current developments, and rapidly growing applications of iminoboronate and salicylhydroxamic–boronate conjugate esters are deliberated. Abstract : Recently, reversible click reactions have found numerous applications in chemical biology, supramolecular chemistry, and biomedical applications. Boronic acid (BA)-mediated cis -diol conjugation is one of the best-studied reactions among them. An excellent understanding of the chemical properties and biocompatibility of BA-based compounds has inspired the exploration of novel chemistries using boron to fuel emergent sciences. This topical review focuses on the recent progress of iminoboronate and salicylhydroxamic–boronate constituted reversible click chemistries in the past decade. We highlight the mechanism of reversible kinetics and its applications in chemical biology, medicinal chemistry, biomedical devices, and material chemistry. This article also emphasizes the fundamental reactivity of these two conjugate chemistries with assorted nucleophiles at variable pHs, which is of utmost importance to any stimuli-responsive biological and material chemistry explorations.